The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1088/0963-0252/20/2/024007
|View full text |Cite
|
Sign up to set email alerts
|

Non-equilibrium kinetics in N2discharges and post-discharges: a full picture by modelling and impact on the applications

Abstract: The main concerns associated with the establishment of a self-consistent model for N 2 discharges and post-discharges at low pressures (typically p ∼ 1 Torr), as well as in mixtures of this gas with O 2 and CH 4 are analysed and discussed. The focus is given on the coupling of the various kinetics involved: electrons, vibrational molecules N 2 (X 1 + g , v), dissociated atoms N( 4 S), ionic species, and various atomic and molecular electronic states. The impact of N 2 -O 2 and N 2 -CH 4 systems on the applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 74 publications
2
27
0
Order By: Relevance
“…Problems arise when electronically and vibrationally excited states exchange their energy in a series of new processes, whose role is still to be understood, despite the numerous important kinetics contributions given by the Lisbon group …”
Section: Resultsmentioning
confidence: 99%
“…Problems arise when electronically and vibrationally excited states exchange their energy in a series of new processes, whose role is still to be understood, despite the numerous important kinetics contributions given by the Lisbon group …”
Section: Resultsmentioning
confidence: 99%
“…The contribution of N 2 (A) to the NO production has been verified by laboratory evidences (Loureiro et al, 2011;Pintassilgo et al, 2009). The NO production form N 2 (A) is through a channel of the reaction between N 2 (A) and the ground state atomic oxygen…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, the electronically excited state of nitrogen, N 2 (A), has been recognized in the recent decades as a significant contributor to thermospheric NO production through owing to its long radiative lifetime in the low‐pressure environment in the thermosphere (Gatilova et al, ; Guerra et al, ; Ionikh et al, ; Kutasi et al, ; Loureiro et al, ; Ono & Oda, ; Pintassilgo et al, ; Rousseau et al, ). N2()A+normalO()normalP3NO+normalN()normalD2 …”
Section: No Chemistry In the Thermospherementioning
confidence: 99%
“…An important update to the NO photochemistry here is the inclusion of the electronically excited state of nitrogen, N 2 (A), as an additional source of NO (Gatilova et al, 2007;Guerra et al, 2001;Ionikh et al, 2006;Kutasi et al, 2007;Loureiro et al, 2011;Ono & Oda, 2002;Pintassilgo et al, 2009;Rousseau et al, 2005), implemented as suggested by Yonker (2013). An in-depth discussion of our current understanding of NO photochemistry in the context of a 1-D model can be found in Yonker (2013).…”
Section: Introductionmentioning
confidence: 99%